Pro Kontra Pengaturan Pencegahan dan Penanganan Kekerasan Seksual di Perguruan Tinggi: Tinjauan Perspektif Hukum Islam - Muhammad Akmal Rizki Rivaldi; Anisa Fernanda; Baidhowi Baidhowi (Prodi Hukum Ekonomi Syariah (Muamalah), 2021)
The government through the Ministry of Education, Culture,Research, and Technology issued Ministerial Regulation No. 30 of 2010 to deal with and preventsexual violence. However, the regulation has many pros and cons in the community. One of themis the polemic of the use of the phrase